STOCK CONTROL SYSTEM ON PT. AYAM MERAK - Riyadi Tri Subagya; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2001)
In carrying out real work practices and preparing this paper, the authors obtain abroader knowledge about data processing system on the computerized system and cancompare with the data processing system manually. Given the data processing systemwith a computerized warehouse section can then be expected to facilitate thewarehouse stock control of goods entering derta out systematically and efficiently aspossible.